Serialism and free atonalism land on Brazilian Popular Music : the songs of the LP Clara Crocodilo by Arrigo Barnabé (Per Musi, 2000)
In this article, it is demonstrated that the use of serial procedures in the songs of the LP Clara Crocodilo by Arrigo Barnabé is directly related to the sociological content of the lyrics, in which the underground of the city of São Paulo in the 1970's is portrayed. This investigation also demonstrates that the serial procedures used in Clara Crocodilo represent an affront to tonality, indicating the distortion and disintegration of the tonal center; in the same way, the lyrics portray human beings in their distorted and disintegrated state.